Functional Outcome of Arthroscopic Management of Anterior Cruciate Ligament Injury using Four-strand Hamstring Tendon Graft: A Prospective Cohort Study - R Kavin Kumar; M Mohan; C Rishab; L Sabari Vaasan (Journal of Clinical and Diagnostic Research)
Introduction: Anterior Cruciate Ligament (ACL) injuries are common, particularly among athletes and can significantly affect an individual’s functional abilities and sports career. ACL reconstruction using a four-strand hamstring tendon graft has become the gold standard for restoring knee stability and function. Aim: To assess the functional outcomes resulting from arthroscopic ACL reconstruction using a four-strand hamstring tendon graft. Materials and Methods: This prospective cohort study was conducted at SRM Medical College and Hospital, Chennai, Tamil Nadu, India, including 33 patients with Grade II and Grade III ACL tears with or without associated meniscal injuries, who underwent ACL reconstruction using a four-strand hamstring tendon graft. The study population included patients aged 20-55 years, with follow-up assessments conducted at three and six months postoperatively. Knee function was measured using the Tegner Lysholm Knee Score, and pain levels were assessed using the Visual Analogue Scale (VAS). Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) version 16.0, employing Analysis of Variance (ANOVA) to evaluate clinical outcomes. Results: The majority of patients, i.e., 18 (54.55%), were between 21 and 30 years of age. Most of the participants were male, 29 (87.88%). The involvement of the right knee was slightly higher, with 17 (51.52%) compared to the left knee, which had 16 (48.48%). Isolated ACL tears were diagnosed in 21 (63.64%) of the patients. The Tegner Lysholm Knee Score improved significantly from a preoperative mean of 35.97 to 71.97 at three months and 88.85 at six months (p-value<0.0001). Pain, as measured by VAS, showed a significant reduction from the second postoperative day to the six-month follow-up (p-value<0.0001). Conclusion: ACL reconstruction using a four-strand hamstring tendon graft resulted in significant improvements in knee function and a reduction in pain within six months of surgery.